2021
DOI: 10.1158/1078-0432.ccr-20-4226
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Features of Cancer-associated Fibroblast Subtypes and their Implication on Cancer Pathogenesis, Prognosis, and Immunotherapy Resistance

Abstract: Purpose: Cancer associated fibroblasts (CAFs) are an important component of the tumor microenvironment (TME), but a systematic investigation of their molecular characteristics and clinical relevance are lacking. Here, we sought to compare CAFs across multiple cancer types to identify critical molecular pathways activated in CAF subtypes, which may contribute to clinical outcome, disease progression, and immunotherapy resistance. Experimental Design:We performed integrated analysis of CAFs from melanoma (MEL), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
202
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(217 citation statements)
references
References 54 publications
14
202
1
Order By: Relevance
“…5 A). Among these targets, MYH11, FN1, COL6A1 markers of CAF subpopulation determined by single-cell sequencing [ 34 ] are upregulated in high CAF group. Consistent with DEG in RNA-seq data, EMT marker CDH1 (E-cadherin) is downregulated, and TGF-beta/BMP pathway protein ACVRL1 [ 35 ] is increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A). Among these targets, MYH11, FN1, COL6A1 markers of CAF subpopulation determined by single-cell sequencing [ 34 ] are upregulated in high CAF group. Consistent with DEG in RNA-seq data, EMT marker CDH1 (E-cadherin) is downregulated, and TGF-beta/BMP pathway protein ACVRL1 [ 35 ] is increased.…”
Section: Resultsmentioning
confidence: 99%
“…Among these targets, MYH11, FN1, COL6A1 markers of CAF subpopulation determined by single-cell sequencing [34] What motivated us to reemphasize the importance of P13K/AKT pathway is Rictor, the core protein of mTOR2 complex who is responsible for AKT phosphorylated activation at serine 473 (Ser473) has remarkably higher expression level in high CAF samples [36]. However, mRNA expression is roughly the same implying high We examined the prognostic performance of these protein targets by survival analysis.…”
Section: Differential Proteomic and Mi-rna Expression In Varied Caf Contextmentioning
confidence: 99%
“…High expression of α-SMA has been proposed as a marker for activated fibroblasts, and a higher expression of α-SMA has been shown in CAFs compared to normal fibroblasts [52]. However, during the last years, there has been published data showing different populations of CAFs with different properties and with different expression of for example α-SMA and BMP4 [53,54]. In this study, we found a higher expression of α-SMA in the HNSCC biopsies than in non-cancerous oral tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A mouse model with a macrophage-specific Foxm1 deletion (mac Foxm1 −/− ) demonstrated decreased macrophage recruitment and migration to lung tumors and ultimately reduced the number and size of lung tumors formed [ 250 ]. In cancer-associated fibroblasts (CAFs), FOXM1 and its downstream targets are upregulated in several cancers [ 251 ] and hepatocellular carcinoma CAFs rely on FOXM1 to activate cartilage oligomeric matrix protein ( COMP ) gene expression, which eventually increases EMT, invasion, and stemness of hepatocellular carcinoma cells [ 252 ]. The recent development of mouse models that recapitulate TME observed in human ovarian cancer [ 253 , 254 ] provides a ripe opportunity to study the role of FOXM1 in the ovarian cancer TME.…”
Section: Foxm1 Oncogenic Functionsmentioning
confidence: 99%